Absolute quantification of Mycoplasma pneumoniae in infected patients by droplet digital PCR to track disease severity and treatment efficacy - Zhao, Hanqing; Yan, Chao; Feng, Yanling; Du, Bing; Feng, Junxia; Cui, Xiaohu; Cui, Jinghua; Gan, Lin; Fan, Zheng; Xu, Ziying; Fu, Tongtong; Yu, Zihui; et al. (Frontiers in Microbiology, 2023)
Mycoplasma pneumoniae is a common causative pathogen of community-acquired pneumonia. An accurate and sensitive detection method is important for evaluating disease severity and treatment efficacy. Digital droplet PCR (ddPCR) is a competent method enabling the absolute quantification of DNA copy number with high precision and sensitivity. We established ddPCR for M. pneumoniae detection, using clinical specimens for validation, and this showed excellent specificity for M. pneumoniae. The limit of detection of ddPCR was 2.9 copies/reaction, while that for real-time PCR was 10.8 copies/reaction. In total, 178 clinical samples were used to evaluate the ddPCR assay, which correctly identified and differentiated 80 positive samples, whereas the real-time PCR tested 79 samples as positive. One sample that tested negative in real-time PCR was positive in ddPCR, with a bacterial load of three copies/test. For samples that tested positive in both methods, the cycle threshold of real-time PCR was highly correlated with the copy number of ddPCR. Bacterial loads in patients with severe M. pneumoniae pneumonia were significantly higher than those in patients with general M. pneumoniae pneumonia. The ddPCR showed that bacterial loads were significantly decreased after macrolide treatment, which could have reflected the treatment efficacy. The proposed ddPCR assay was sensitive and specific for the detection of M. pneumoniae. Quantitative monitoring of bacterial load in clinical samples could help clinicians to evaluate treatment efficacy.